1985
DOI: 10.2307/3801860
|View full text |Cite
|
Sign up to set email alerts
|

Fecal Indices to Dietary Quality of Cervids in Old-Growth Forests

Abstract: JSTOR is a not-for-profit service that helps scholars, researchers, and students discover, use, and build upon a wide range of content in a trusted digital archive. We use information technology and tools to increase productivity and facilitate new forms of scholarship. For more information about JSTOR, please contact support@jstor.org. . Wiley, Wildlife Society, Allen Press are collaborating with JSTOR to digitize, preserve and extend access to The Journal of Wildlife Management. Determination of dietary qual… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

1
69
2
1

Year Published

1997
1997
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 107 publications
(73 citation statements)
references
References 22 publications
1
69
2
1
Order By: Relevance
“…Islam et al [2011] reported a high correlation between NDVI and nitrogen content of maize plants, but only at one specific phenological stage (8-leaf stage). Other studies linked NDVI with faecal crude protein (FCP) of large herbivores, which is considered a reliable indicator of the quality of vegetation [Cordova et al, 1978;Leslie and Starkey, 1985;Hodgman et al, 1996]. For example, Ryan et al [2012] showed a positive relationship between log transformed NDVI and nitrogen faecal content of African Buffalo (Syncerus caffer) and Hamel et al [2009] found a negative relationship between integrated NDVI in June and the date of the peak in FCP of mountain goats (Oreamnos americanus) and bighorn sheep (Ovis canadensis).…”
Section: Introductionmentioning
confidence: 99%
“…Islam et al [2011] reported a high correlation between NDVI and nitrogen content of maize plants, but only at one specific phenological stage (8-leaf stage). Other studies linked NDVI with faecal crude protein (FCP) of large herbivores, which is considered a reliable indicator of the quality of vegetation [Cordova et al, 1978;Leslie and Starkey, 1985;Hodgman et al, 1996]. For example, Ryan et al [2012] showed a positive relationship between log transformed NDVI and nitrogen faecal content of African Buffalo (Syncerus caffer) and Hamel et al [2009] found a negative relationship between integrated NDVI in June and the date of the peak in FCP of mountain goats (Oreamnos americanus) and bighorn sheep (Ovis canadensis).…”
Section: Introductionmentioning
confidence: 99%
“…Researchers have used faecal nutrient concentration studies in a variety of indigenous types of wildlife as well as for domestic livestock (Erasmus et al 1978;Belonje & Van den Berg 1980;Holechek et al 1982Holechek et al , 1985Leslie & Starkey 1985;Leite & Stuth 1990;Irwin et al 1993;Grant et al 1995Grant et al , 1996Grant et al , 2000MacLeod et al 1996;Vorster 1996;Wrench et al 1996Wrench et al , 1997Van der Waal et al 2003;Codron et al 2005;Botha & Stock 2005;Mbatha & Ward 2006). Leslie & Starkey (1985) found that faecal nitrogen concentration increases with an increase of the nitrogen concentration of the herbivore's diet. Total faecal nitrogen is reported to correlate with the soluble nitrogen fraction in faeces (Leite & Stuth 1990) although the ratio of insoluble nitrogen in faeces increases as the forage quality decreases (Leite & Stuth 1990).…”
Section: Introductionmentioning
confidence: 99%
“…Common problems that hamper the determination of diet quality and animal condition include animal selectivity, and the cost, ethics and duration of using intrusive methods such as oesophageal fistulae (Leslie & Starkey 1985;Wrench et al 1997;Botha & Stock 2005). These factors make dietary quality one of the most difficult aspects of range nutrition to study .…”
Section: Introductionmentioning
confidence: 99%
“…Experimental studies with cattle and sheep showed different regression line slopes between grass and legumes (Wehausen 1995). Regression lines for elk are likely to be different in slope between diets with and without browse, although this was not statistically demonstrated (Leslie and Starkey 1985). Conversely, no difference was found in linear regression equations between grassland and forest areas for cattle (Holechek et al 1982).…”
mentioning
confidence: 71%
“…Despite the suggestions of these experimental studies, the simple linear relationship between FN and DN has been verified in cattle fed both grass and browse in captivity (Holechek et al 1982), as well as in captive black-tailed deer Odocoileus hemionus columbianus and mule deer O. h. hemionus fed a mixture of grass and browse (Mubanga et al 1985, Hodgman et al 1996 and in North American elk, black-tailed deer, and sika deer Cervus nippon Heude, 1884 fed both grass and browse in the field (Leslie and Starkey 1985, Watanabe and Takatsuki 1993, but see Hobbs 1987. FN reflected the nutritional status of free-ranging deer on winter ranges, where browsing was common (Hodgman and Bowyer 1986).…”
mentioning
confidence: 99%